Evaluation of Professional Self-esteem among EFL Teachers and Students at Mevlana University - KHEZERLOU, Ebrahim (Journal of History Culture and Art Research, 2014)
Evaluation of Professional Self-esteem among EFL Teachers and Students at Mevlana University Abstract Self-esteem is generally defined as a global self-evaluation. It indicates the extent to which an individual believes the self to be capable, significant, successful and worthy (Rosse et al., 1991; Leary and McDonald, 2003). The study generally aims at measuring and correlating professional self-esteem perceptions of ELT professors (N = 6) and prospective EFL teachers (N = 79) at Mevlana University for diagnosing the pedagogical problems. Four professional self-esteem scales, each including 16 items, were developed to measure the participants’ self-esteem perceptions in the five areas of (a) satisfaction, (b) knowledge development, (c) practice, (d) adaptation, and (e) communication. The average internal consistency reliability of the four scales was r = 0.86. The findings revealed that there were statistically significant differences between the socio-demographic variables of Gender and Student-class and Student Self-report Self-esteem and between the socio-demographic variable of Student-class and Teacher Student-report Self-esteem. Moreover, they demonstrated slight positive correlation between Teacher Self-report Self-esteem and Teacher Student-report Self-esteem and moderate negative correlation between Student Self-report Self-esteem and Student Teacher-report Self-esteem. Finally, the regression findings showed that Student Self-report Self-esteem was better predicted by the Practice dimension, while Student Teacher-report Self-esteem by the development dimension.